Perancangan Dudukan Pelat Adjustable Holder sebagai Sarana Penunjang Mesin Roll di PT. Boma Bisma Indra Pasuruan - Felicia Zafirah; George Endri Kusuma; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
In the roll bending process, sheet metal is straightened before rolling. With plates of fairly large dimensions, 6m to 8m in length and 1.5m to 2.5m in width, the alignment process is not easy and takes a lot of time. In this study, we designed an adjustable plate holder to overcome this problem. The design method used is Ulrich's method by creating his three design concepts which later select the best design according to selection criteria. The design of this tool used Fusion 360 software to perform a strength analysis to determine the number of stresses obtained for the loads received and functional analysis to determine if this tool is expected by running torque theory. Make sure it works according to the functions provided. Based on the selected design concept, the strength of the adjustable holder plate structure was analysed and the maximum stress value was 9,662 MPa. This adjustable plate holder can shorten the straightening process to 61 seconds. The total budget required to manufacture this tool is Rp 17,918,000.00. In future research, it is expected to take into account the overall loading and fabrication carried out to obtain more specific results.